Penerapan Regresi Data Panel dalam Penentuan Determinan Pertumbuhan Ekonomi Pulau Jawa pada Masa Pandemi Covid-19 - Dio Dwi Saputra (Seminar Nasional Official Statistics, 2022)
The Covid-19 pandemic has had a major impact on the condition of the world economy, including Indonesia. Based on Statistics Indonesia data, the Indonesian economy is dominated by the economy of Java Island, which reached 58.75% in 2020. Thus, this study aims to know the determinants of economic growth on Java Island during the Covid-19 pandemic. The method used in this study is a descriptive statistical method, in the form of graphical display and statistical inferential method using panel data regression modeling. The findings of this study are that of the three independent variables used, only one independent variable affects the economic growth of Java Island during the Covid-19 pandemic, namely the room occupancy rate of the star hotel. There is an increase in the room occupancy rate in star hotels by 1%, which it will increase the economic growth of Java Island by 0.2359%. Thus, it was concluded that the tourism sector contributed positively to the economic growth of Java Island during the Covid-19 pandemic. However, even though the other two independent variables are not significant, the government still has the optimize these two variables